RNase H As Gene Modifier, Driver of Evolution and Antiviral Defense - Moelling, Karin; Broecker, Felix; Russo, Giancarlo; Sunagawa, Shinichi (Frontiers in Microbiology, 2017)
Retroviral infections are ‘mini-symbiotic’ events supplying recipient cells with sequences for viral replication, including the reverse transcriptase (RT) and ribonuclease H (RNase H). These proteins and other viral or cellular sequences can provide novel cellular functions including immune defense mechanisms. Their high error rate renders RT-RNases H drivers of evolutionary innovation. Integrated retroviruses and the related transposable elements (TEs) have existed for at least 150 million years, constitute up to 80% of eukaryotic genomes and are also present in prokaryotes. Endogenous retroviruses regulate host genes, have provided novel genes including the syncytins that mediate maternal-fetal immune tolerance and can be experimentally rendered infectious again. The RT and the RNase H are among the most ancient and abundant protein folds. RNases H may have evolved from ribozymes, related to viroids, early in the RNA world, forming ribosomes, RNA replicases and polymerases. Basic RNA-binding peptides enhance ribozyme catalysis. RT and ribozymes or RNases H are present today in bacterial group II introns, the precedents of TEs. Thousands of unique RTs and RNases H are present in eukaryotes, bacteria, and viruses. These enzymes mediate viral and cellular replication and antiviral defense in eukaryotes and prokaryotes, splicing, R-loop resolvation, DNA repair. RNase H-like activities are also required for the activity of small regulatory RNAs. The retroviral replication components share striking similarities with the RNA-induced silencing complex (RISC), the prokaryotic CRISPR-Cas machinery, eukaryotic V(D)J recombination and interferon systems. Viruses supply antiviral defense tools to cellular organisms. TEs are the evolutionary origin of siRNA and miRNA genes that, through RISC, counteract detrimental activities of TEs and chromosomal instability. Moreover, piRNAs, implicated in transgenerational inheritance, suppress TEs in germ cells. Thus, virtually all known immune defense mechanisms against viruses, phages, TEs, and extracellular pathogens require RNase H-like enzymes. Analogous to the prokaryotic CRISPR-Cas anti-phage defense possibly originating from TEs termed casposons, endogenized retroviruses ERVs and amplified TEs can be regarded as related forms of inheritable immunity in eukaryotes. This survey suggests that RNase H-like activities of retroviruses, TEs, and phages, have built up innate and adaptive immune systems throughout all domains of life.